A Comparison of Muslim Millennial Students' Religiousity at Islamic and Non-Faith Based Universities - Suzanawaty, Leis; Aisyah, Muniaty; Umiyati, Umiyati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThe purpose of this study was to assess the influence of learning in a higher education institution and the type of institution, on the religiosity of Muslim Millennial students in Indonesia. In this study, religiosity is defined using an Islamic theoretical framework and divided into two sub-variables: hablumminallah and hablumminannas behavior, which serve as dependent variables hablumminallah behavior also serve as an intervening variable. Thus, this work used the Structural Equation Modeling technique using 292 samples to analyze direct and indirect influences. The findings indicated that higher educational institutions directly affect the habluminallah behavior, but not on the habluminannas behavior. While this has an indirect effect on hablumminannas behavior, it is mediated by hablumminallah behavior. It suggests that the level of students' hablumminallah behavior, which is high, makes the higher educational institutions potentially affect the students' hablumminannas too. Moreover, this study used the One-way Anova test to determine whether there are differences in the socio-religious milieu and student religiosity of Islamic and non-faith-based universities. The findings indicate that religious facilities are superior in non-faith-based universities to those in Islamic universities, whereas Islamic subject professors' roles and management support are identical. , there is no difference in the behavior of hablumminallah and hablumminannas students. This shows that if a university provides adequate religious facilities, both Islamic and non-faith-based universities will encourage students' religiosity similarly. AbstrakPenelitian ini bertujuan menganalisis pengaruh perguruan tinggi terhadap religiusitas mahasiswa muslim milenial di Indonesia. Penelitian ini menggunakan kerangka teori dengan pendekatan Islami dimana religiusitas terbentuk dari dua sub variabel yaitu perilaku habluminallah dan hablumminannas sebagai variabel terikat, dimana perilaku hablumminallah juga sebagai variabel antara. Karenanya, untuk dapat menganalisis pengaruh langsung dan tidak langsung, penelitian ini menggunakan teknik Structural Equation Modelling dengan 292 sampel. data. Hasilnya menunjukkan bahwa secara langsung, perguruan tinggi hanya mempengaruhi perilaku habumminallah mahasiswa, namun tidak perilaku hablumminannasnya. Sedangkan secara tidak langsung, perguruan tinggi mampu mempengaruhi perilaku hablumminannas mahasiswanya yang dimediasi oleh perilaku hablumminallahnya. Hal ini mengindikasikan bahwa perilaku hablumminallah mahasiswa yang tinggi, menjadikan perguruan tinggi berpotensi mempengaruhi perilaku hablumminanas mahasiswanya pula. Penelitian ini juga melakukan uji One-way Anova untuk menganalisis apakah terdapat perbedaan kondisi sosial keagamaan di lingkungan kampus dan perilaku religius mahasiswa di universitas Islam dengan di universitas Umum. Hasilnya menunjukkan bahwa fasilitas keagamaan di universitas Umum lebih tinggi dibandingkan universitas Islam. Yang mengejutkan, tidak terdapat perbedaan perilaku habluminallah maupun hablumminannas antara mahasiswa universitas Islam dengan Umum. Hal ini mengimplikasin bahwa, jika fasilitas keagamaan di lingkungan universitas memadai, maka baik universitas Islam maupun Umum akan efektif mempengaruhi religiusitas mahasiswanya.How to Cite: Suzanawaty, L., Aisyah, M., Umiyati. (2021). A Comparison of Muslim Millennial Students' Religiousity at Islamic and Non-Faith Based Universities. TARBIYA: Journal of Education in Muslim Society, 8(1), 44-56. doi:10.15408/tjems.v8i1.19210.